Economic perspectives on nuclear desalination deployment in the MENA region - Shatha Alyazouri; Ammar Alkhalidi (International Journal of Thermofluids)
Most countries of the Middle East and North Africa (MENA) region suffer from water scarcity and stress, especially in areas with high solar isolation and hot weather. Nuclear energy offers many potentials, including low-cost, large-scale supply, eco-friendly energy production, and optimal alternatives to depleted fossil fuel-based energy production. This study conducts a preliminary economic analysis of nuclear desalination, focusing on three reactor technologies of interest in the MENA region —APR-1400, HTR-PM, and SMART— each coupled with Reverse Osmosis (RO) and Multi-Effect Distillation (MED) methods. Utilizing the Desalination Economic Evaluation Program (DEEP) model, the indicative analysis reveals that high-temperature helium-cooled reactors exhibit the most cost-effective outcomes for both MED and RO desalination. Generally, RO desalination systems demonstrate lower costs than MED options. Significantly, all scenarios fall within an economically viable range of 0.69 to 1.04 $/m³. Moreover, a sensitivity analysis shows that RO desalination processes are more sensitive to the salinity of the feedwater.